(untitled) (UNED Research Journal, 2018)
The current population decline of amphibians, mainly due to habitat destruction and alteration by humans, is alarming. From March to May 2017, we searched for amphibians in terrestrial and arboreal bromeliads (>20cm in height) in 16ha of pine-oak forest. Out of 3 467 bromeliads, only two specimens had amphibians, indicating a devastating population decline.